E-Duality Results For E-Differentiable E-Invex Multiobjective Programming Problems - Abdulaleem, Najeeb (Journal of physics. Conference series, 2019)
In this paper, a class of E-differentiable multiobjective programming problems with both inequality and equality constraints is considered. The so-called vector Mond-Weir E-dual problem and vector mixed E-duality problem are defined for the considered E-differentiable multiobjective programming problem with both inequality and equality constraints and several Mond-Weir and mixed E-duality theorems are established under (generalized) E-invexity hypotheses.